Efektifitas Penerapan MAKP Primary Nursing dalam Meningkatkan Mutu Pelayanan dan Kepuasan Pasien: Literature Review - Raya Harianja; Catharina Dwiana Wijayanti (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The Primary Nursing Professional Care Model (MAKP) is an approach to providing nursing care that emphasizes responsibility, continuity, and professionalism of nurses in delivering comprehensive care. The application of this method is believed to improve the quality of nursing services and patient satisfaction; however, research findings remain diverse, indicating the need for further study. Purpose: This literature review aims to analyze the effectiveness of the implementation of MAKP Primary Nursing in improving the quality of nursing services and patient satisfaction, assessed through pre- and post-intervention comparisons. Method: The study uses a literature review approach with the PICOT framework (Population, Intervention, Comparison, Outcome, Time). Data were collected from primary sources indexed in databases such as Google Scholar and PubMed. Inclusion criteria consisted of quantitative studies published between 2020 and 2025 that discuss MAKP Primary Nursing, nursing service quality, and patient satisfaction. Irrelevant studies were excluded, and the selected articles were analyzed using descriptive and thematic methods. Results: The findings indicate that the implementation of MAKP Primary Nursing has a positive impact on improving nursing service quality, particularly in continuity of care, therapeutic communication, patient safety, and documentation. In addition, most studies report a significant increase in patient satisfaction, especially in empathy, responsiveness, and service reliability. Conclusion: MAKP Primary Nursing is effective in improving the quality of nursing services and patient satisfaction, and it is recommended for continuous implementation in healthcare settings to enhance service quality and nurse professionalism.